Tafsir Lisan Amar Makruf Nahi Mungkar: Kajian Perspektif Ḥabā`Ib di Kota Pontianak Kalimantan Barat - Akbar, Taufik; Ilmi, Syaiful (Alif Lam : Journal of Islamic Studies and Humanities, 2024)
This article explores the oral interpretation of amar makruf nahi mungkar from the perspective of ḥabā`ib in Pontianak City, West Kalimantan. The study is qualitative in nature and adopts a field research model with descriptive-analytic data analysis. The findings suggest that local ḥabā`ib interpretations of amar makruf nahi mungkar can be classified into two groups: those that specifically focus on Quranic texts containing the phrase, and those that interpret verses of the Quran without the phrase. The discussion of the term ‘munkar’ predominantly revolves around issues relating to Muslim and non-Muslim leaders, the criminalization and humiliation of ulama, and LGBT-related cases. The oral tradition plays a crucial role in shaping the interpretation of ḥabā`ib, which is characterized by three key aspects: a) a focus on local issues, b) an agonistic tone, and c) conservative or traditionalist views. These characteristics have a significant impact on the interpretation of amar makruf nahi mungkar by ḥabā`ib, resulting in an interpretation that differs from that found in traditional interpretation literature.